AB1161 An Assessment of Methotrexate-Related Patient Knowledge. (9th June 2015) - Mehta, P.; Carlucci, F.; Mackworth-Young, C.; Carulli, M.; Haskard, D.
Abstract : Background: Methotrexate (MTX) is the most-widely prescribed first-line disease modifying anti-rheumatic drug (DMARD) for rheumatoid arthritis, used as mono or combination therapy or as an anchor with biologics. Potential adverse effects, may lead to drug discontinuation and may include preventable, serious or fatal incidents. Patient education is intrinsic to informed consent and patient safety. A number of agencies have published guidelines emphasising MTX patient education, including the National Patient Safety Agency (NPSA) in the U.K. and the Institute for Safe Medication Practices in the United States. Objectives: To assess patient knowledge, as defined by national standards presented in the Arthritis Research UK MTX patient information leaflet. Methods: Questionnaires were distributed to 100 consecutive patients attending the Rheumatology outpatient clinic at two London teaching hospitals in 2013. Results: 67% patients were female. The mean age was 46.7 years (range 18-82 years) and the mean duration of MTX therapy was 9 years (range 0.3-25 years). In 19% cases, English was not the first language and 12% did not have any educational qualifications. 16% thought that MTX was a steroid or a painkiller, 11% were unaware of their prescribed dose. 36% stated that MTX was being prescribed in both primary and secondary care and 14% were unsure of who was responsible for blood monitoring. Of the 57% patients that had an NPSA MTX monitoring booklet, only 21% stated that their doctor/nurse and 57% of their pharmacists asked to see it. 9% patients thought that folic acid was a painkiller or an anti-inflammatory medication. 6% were taking folic acid on the same day as MTX and 4% were not taking any folic acid. 98% patients were aware of the potential hepatotoxic effects, 84% of myelosuppressive effects and 83% of possible oral ulceration. Some patients attributed other adverse effects to MTX – kidney failure (27%), poor memory (9%), hypertension (9%) and diabetes (5%). Only 44% patients knew that they should have annual influenza vaccination and avoid live vaccines. 14% considered all vaccines to be contraindicated. Most women were aware of pregnancy and breast-feeding implications, but only 54% women and 49% of males were aware of recommendations for males regarding conception. Conclusions: Our results demonstrate deficiencies in patient knowledge of MTX and safety, despite all patients receiving doctor or nurse-delivered education prior to initiating treatment. Although the questionnaire used was not validated we had a 92% questions were completed and our findings highlight a need to improve current approaches to patient education, in order to improve patient safety. We have already implemented signed consent for blood monitoring. Strategies to aid recall and retention could include written information with multi-lingual translations, the development of multimedia educational material, signing consent forms before starting MTX, patient feedback on education received, testing patient knowledge, targeted re-education and encouraging patients, primary care physicians and pharmacists to use the NPSA MTX monitoring booklet. Disclosure of Interest: None declared